HUBUNGAN KELEKATAN DENGAN KECERDASAN EMOSI DAN PENYESUAIAN SOSIALPADA ANAK USIA DINI - henni anggraini; sarah emmanuel (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
Attachment  is  is  the  tendency  and  desire  of  an  individual  is  a  child  to  seek  proximity with  their  guardians  (Monk  et  all,  2004).There  are  four  basic  principles  of  the  bond between  parent  and  child  is  the physical  needs  of  children  for  food  and  warmth  that  filled by  their  mother,  the  encouragement  of  origin  which  is  owned  by  the  child  to  cling  to  the mother's  chest,  the  baby  needed  to  touch  and  clung  by  a  person,  and  the  disappointment of the baby as it is expelled from in the womb (Bowlby, 1969). The quality of a relationship between  a  children  and  a  parents  are  an  important  factor  for  development  of  children. The  theory  of  attachment  explained  that  children  need  attachment  with  at  least  one caregiver  to  develop  emotional  and  social  development.  This  study  aims  to  determine  the relationship between  attachment  of  emotional  intelligence  and  social  adjustment  in  early childhood.  This  study  used  quantitative  methods  to  the  subject  35  students  of  class  B  TK muslimat  NU  22  aged  5‐7  years.  The  collecting  of  data  obtained  through  a  scale  of attachment  between  a  child  and  a  parents,  the  scale  of  emotional  intelligence  and  social adjustment.  Furthermore,  the  data  were  analyzed  by  using  Product  Moment  Pearson correlation  analysis  using  SPSS  21.0  for  windows.  The  result  showed  that  there  was  a positive  and  significant  relationship  between  attachment  with  emotional  intelligence  and social adjustment in early childhood (rxy1 = 0,537; rxy2= 0,513; p = 0,005 < 0,05).